Gender-based differences in occurrence of gingival disease among dental students: A survey - Rizwan M Sanadi; Laksha R Chelani; Namrata J Suthar; Nitin Khuller; P Basavaraj (Wolters Kluwer Medknow Publications, 2017)
Background: Females have a more favorable attitude toward health-related issues, including dental health behavior. Many studies have shown gender differences in the occurrence of gingival disease, but a few have clearly explained what causes this difference. Objectives: The present survey was conducted to assess gender differences in the occurrence of gingival disease among dental students, influenced by oral health behaviors and lifestyle factors. Materials and Methods: The survey assessed 209 dental students (59 males and 150 females) aged between 18 and 29 years. The assessment of oral hygiene intraorally was done using plaque index, sulcus bleeding index, and simplified oral hygiene index. Additional information was collected regarding oral health behaviors and lifestyle factors. The results of the survey were subjected to analysis to test the statistical significance. Results: Chi-square test was used to assess the gender differences. It was found that females had better oral health behaviors and a healthier lifestyle (P < 0.001) than males. There were significant differences between males and females (P < 0.001) when the oral health status was compared. Conclusion: Gender-based differences in gingival disease among dental students were found to be significant in this survey. This can be explained by oral health behaviors and hygiene status, which is influenced by lifestyle factors. Hence, different approaches to males and females may be helpful in preventing gingival disease.